Predicting temperature of major cities using machine learning and deep learning - Jaharabi, Wasiou; Hossain, MD Ibrahim Al; Tahmid, Rownak; Islam, Md. Zuhayer; Rayhan, T.M. Saad (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.